Dietary glycerol monolaurate improved the growth, activity of digestive enzymes and gut microbiota in zebrafish (Danio rerio) - Yuchao Wang; Abdullah; Hao Zhong; Jing Wang; Fengqin Feng (Aquaculture Reports, 2021)
Microbial recurrent infections and antimicrobial resistance have motivated the researchers to explore bioactive compounds as safe alternative antimicrobials to target pathogenic microorganisms. Interest in finding new biologically active substances to replace conventional antibiotics in aquatic feed has rapidly increased, since the misuse or overuse of antibiotics produced antibiotic resistance. Glycerol monolaurate (GML), has attracted attention of researchers due to its growth-promoting and immunomodulatory potential by exerting beneficial effects on the gut microbiota and host health. This study aimed to evaluate the effects of dietary GML using as a feed additive on the growth performance, blood lipid profile, hepatic lipid deposition, body composition, digestive enzymes, serum anti-inflammatory activities, and gut microbiota of zebrafish. The study’s findings showed that diet supplemented with 750 mg kg−1 of GML, significantly improved the growth performance, feed utilization and intestinal lipase activity, as well as body crude lipid content without inducing hepatic fat accumulation. GML supplementation also promoted the serum anti-inflammatory potential by elevating the level of TGF-β1 and IL-10. Moreover, dietary supplementation of GML positively restructured the intestinal microbial ecology by improving the relative abundance of several favorable bacteria, including Cetobacterium, Shewanella, and Vibrio at the genus level. Conclusively, study’s findings suggest that GML supplementation contributes in improving the growth, digestive enzymes activities, anti-inflammatory potential, and gut microbiota, indicating GML promising potential as a feed additive in aquaculture nutrition.